Strategi UMKM CV. Najwa dalam Meningkatkan Daya Saing Pemasaran Pie Susu Khas Bali - Fauzi, M. Asif Nur; Rohmah, Yusfika Fatimatur; Khoiriyah, Khoiriyah; Machrus, Ali; Nuruddin, Nuruddin (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are considered to be the driving force of the economy in Indonesia, especially in Denpasar. This can be seen from the large amount of state foreign exchange income coming from MSMEs. In the last decade, many micro businesses have emerged, whether in the form of culinary businesses, fashion, agribusiness, and others. Research with the title